Coronary artery status in patients with coronary heart disease and chronic obstructive pulmonary disease: results of selective coronary angiography - N. Yu. Grigorieva; E. G. Sharavrin; A. N. Kuznetsov; T. V. Koroleva; P. A. Blinov; E. B. Shakhov (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To study the specifics of coronary artery pathology in patients with coronary heart disease (CHD) and chronic obstructive pulmonary disease (COPD), using the data of selective coronary angiography (CAG). Material and methods. In total, 907 CHD patients were examined. Group I included 251 participants with CHD and COPD; Group II included 656 individuals with CHD only. CAG was performed in 582 patients (64,2%): 184 from Group I (73,3%) and 398 from Group II (60,7%). Results. In patients with the combination of cardiac and pulmonary disease, the prevalence of two- and three-vessel pathology was higher, compared to CHD-only patients: 70,6% in Group I vs. 53,8% in Group II (p=0,002). In Group I, the Syntax Scale score was significantly higher than in Group II (24,7±4,1 vs. 18,7±3,1, respectively). Conclusion. Patients with combined cardiac and pulmonary pathology demonstrated a more severe coronary artery atherosclerosis, based on such CAG parameters as stenosis degree, number of involved vessels, size and location of lesions, and proximal stenosis.